Sosialisasi Permainan Tradisional Bakiak Pada Usia Kanak-Kanak 7-8 Tahun Di Desa Teluk Lada - Nurul Munajiyah; Idris Supriadi; Devaron Suardi; Sukron Ma'mun; Rusmiyadi (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
The traditional bakiak game is one of the traditional bakiak games with the aim of increasing interest in playing the traditional bakiak game. Besides that, traditional bakiak games also increase cooperation with groups. Traditional bakiak games can help shape the character of mutual cooperation and cooperation with teams or groups.If the traditional bakiak game is of interest to many children, it will have many positive impacts. Bakiak traditional games can create good traits or characters, one of which is mutual cooperation with the team or group. Traditional games are rarely played nowadays, but this socialization is held to increase interest in playing the traditional bakiak game again.